2018
DOI: 10.1590/1981-22562018021.170136
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of participants and non-participants of public physical exercise programs

Abstract: Objective: to compare the quality of life of elderly participants and non-participants of public physical exercise programs. Method: a control, analytical and cross-sectional study analyzing 108 elderly participants of public exercise programs (SG) and 126 non-participants (CG) in the city of Goiânia, Goias, Brazil, was performed. An initial Assessment Form, the Mental State Mini-Exam, the short version of the International Physical Activity Questionnaire, the World Health Organization Quality of Life - Bref … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
5
0
5
Order By: Relevance
“…Our findings on the dimensions of quality of life in older adults of both countries were consistent with previous studies carried out in other Latin-American countries such as Brazil [ 74 ], Chile [ 68 ], Peru [ 42 , 75 ], and Mexico itself [ 41 ]. Specifically, the levels of quality of life of the Mexican older adults reported in our study are similar to those shown by González-Celis and Gómez-Benito [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on the dimensions of quality of life in older adults of both countries were consistent with previous studies carried out in other Latin-American countries such as Brazil [ 74 ], Chile [ 68 ], Peru [ 42 , 75 ], and Mexico itself [ 41 ]. Specifically, the levels of quality of life of the Mexican older adults reported in our study are similar to those shown by González-Celis and Gómez-Benito [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…The data pointed out that the sample, in a general way, got levels of daily physical activities not sufficiently to be considered actives, and it can be associated with the lower results in the frailty and functional autonomy tests. This correlation between physical activity and functional autonomy has already been pointed out by other researches (Baptista, 2018;Costa, Rodrigues, Prudente, & Souza, 2018;Pereira de Llano et al, 2017), and here it seems was proved.…”
Section: Discussionsupporting
confidence: 82%
“…The literature has pointed out that physical training programmes with different exercise modalities, focusing on balance training, muscle strength, flexibility and endurance, is the most effective and cost-effective fall-prevention strategy in older populations because it can reduce both the number of individuals that fall and the fall rate in fallers [ 17 ]. The Brazilian National Policy on Health Promotion recognizes the importance of physical activities and practices involving the body in reducing health risks and improving the quality of life of individuals [ 55 ]; however, there are few reports in the literature of government programmes aimed at the older population with an evaluation of their impact [ 55 ], as is the case of the “Academy in Town” – a programme implemented in Recife, in Northeast Brazil [ 56 ].…”
Section: Discussionmentioning
confidence: 99%